2016
DOI: 10.12968/jpar.2016.8.6.302
|View full text |Cite
|
Sign up to set email alerts
|

What are family member experiences of the resuscitation of a relative?

Abstract: This study aimed to gain insight into the feelings and perceptions of family members who witness an adult family member resuscitation. Little is known about family members' experiences and their needs and priorities. Resuscitation is a complex and highly emotive situation but guidance for paramedics to support families either in the decision-making process or to remain present is limited. Policy developments around improved and shared decision making are not evident in any guidance for resuscitation for parame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…The sudden transition of mindset described by this participant shows that clinicians mentally separate the resuscitation attempt from the interaction with family. The current research shows that family want inclusion throughout the resuscitation process (Nevins, 2016;Zali et al, 2017). It would appear that the participant has separated herself into two personas in order to fulfil the demands of an OHCA.…”
Section: 'Out Of the Clinical And Into The Human'mentioning
confidence: 75%
See 1 more Smart Citation
“…The sudden transition of mindset described by this participant shows that clinicians mentally separate the resuscitation attempt from the interaction with family. The current research shows that family want inclusion throughout the resuscitation process (Nevins, 2016;Zali et al, 2017). It would appear that the participant has separated herself into two personas in order to fulfil the demands of an OHCA.…”
Section: 'Out Of the Clinical And Into The Human'mentioning
confidence: 75%
“…Barrett and Wallis (1998) found that only 11% of the family members included in their study were offered the chance to be present; yet 62% of the family members would have chosen to be present had they been given the opportunity. A systematic review conducted by Nevins (2016) found that relatives want to remain connected to their loved one and be present throughout the resuscitation. This was mirrored by Zali et al (2017) who found that 57.2% of family members felt it was their right to be present during resuscitation; whereas 62.5% of nurses involved in that study disagreed with FPDR.…”
mentioning
confidence: 99%